The role of learner training in self-access learning - Noor Asmara, Mohammad Yusoff (Universiti Malaysia Sarawak, (UNIMAS), 2004)
This research aims to investigate teachers understanding of learner training with regards to their knowledge and experience in self-access learning. It also aims to investigate the activities of learner training given by teachers which further looks at the techniques mostly addressed in the activities. The respondents were teachers from 10 primary schools in Kuching and Samarahan. The teachers involve in running the self-access centre in their schools. Questionnaire and interview were used to obtain the data, which were analyzed descriptively and converted into percentage. The finding reveals that there were different level of teachers' understanding of the concept of learner training, which was based on their experience and knowledge in SAL with regards to learner training. The finding also shows that the teachers addressed certain techniques in learner training activities in order to develop learners to become independent and responsible for their own learning.